Пошаговое объяснение:
3(х+7)-18=42
3x + 21 - 18 = 42
3x + 3 = 42
3x = 42 - 3
3x = 39
x = 39 : 3
x = 13
3(13+7)-18=42
3*20-18=42
60-18=42
42=42
ответ: х=13
3(х+7)=42+18
3(х+7)=60
х+7=60:3
х+7=20
х=20-7
х=13
Проверяем: 3(13+3)-18=3*20-18=60-18=42, Все верно
Пошаговое объяснение:
3(х+7)-18=42
3x + 21 - 18 = 42
3x + 3 = 42
3x = 42 - 3
3x = 39
x = 39 : 3
x = 13
3(13+7)-18=42
3*20-18=42
60-18=42
42=42
ответ: х=13
Пошаговое объяснение:
3(х+7)-18=42
3(х+7)=42+18
3(х+7)=60
х+7=60:3
х+7=20
х=20-7
х=13
Проверяем: 3(13+3)-18=3*20-18=60-18=42, Все верно